Lolei Tradition In The Perspective Of Islamic Law In Watorumbe Village, Central Buton Regency - Irma Purnamayanti; Ana Muslimah (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
Lolei Tradition in the Perspective of Islamic Law in Watorumbe Village, Central Mawasangka District, Central Buton Regency. The main discussion is formulated into several research questions, namely: a) how is the implementation of the Lolei tradition, and b) what is the perspective of Islamic law on the implementation of the Lolei tradition and c) how is the Lolei tradition reviewed from the aspects of benefits and harms. This study uses a qualitative method, with data collection using observation, interview and documentation techniques. Data analysis by analyzing data reduction and data presentation and drawing conclusions. This study aims to determine the process of implementing the Lolei tradition, and the perspective of Islamic law on the implementation of the Lolei tradition and the Lolei tradition reviewed from the aspects of benefits and harms. The data sources obtained by the author are informants consisting of traditional figures, religious figures and community figures. The results of the study show that the Lolei tradition is in line with Islamic teachings because its implementation is intended to seek protection from Allah SWT. However, in the process of implementing the Lolei tradition there are still parts that conflict with Islamic teachings. Therefore, community leaders, religious leaders, and traditional leaders, as well as the entire community of Watorumbe Village, need to make changes or eliminate parts that conflict with Islamic teachings so that they are in accordance with Islamic law.